Photodynamic Therapy Using Cerenkov and Radioluminescence Light - Spinelli, Antonello E.; Boschi, Federico (Frontiers in Physics, 2021)
In this short review the potential use of Cerenkov radiation and radioluminescence as internal sources for Photodynamic therapy (PDT) is discussed. PDT has been developed more than 100 years ago and is based on the induced photo conversion of a drug called photo sensitizer (PS) that trigger the production of cytotoxic reactive oxygen species (ROS) leading to the killing of the cells. In order to overcome the problem of light penetration in the tissues, different solutions were proposed in the past. The use of radioisotopes like:18F,64Cu,90Y,177Lu as internal light sources allow a reduced light tissue absorption and, thus, possibly enhancing the cytotoxic effect of PDT on cancer cells.